Challenging Communion : The Eucharist and Middle English Literature - Garrison, Jennifer (Professor of English) (Book collections on Project MUSE., 2017)
In this book, Jennifer Garrison examines literary representations of the central symbol of later medieval religious culture: the Eucharist. In contrast to scholarship that depicts mainstream believers as enthusiastically and simplistically embracing the Eucharist, Challenging Communion: The Eucharist and Middle English Literature identifies a pervasive Middle English literary tradition that rejects simplistic notions of eucharistic promise. Through new readings of texts such as Piers Plowman, A Revelation of Love, The Book of Margery Kempe, and John Lydgate's religious poetry, Garrison shows how writers of Middle English often take advantage of the ways in which eucharistic theology itself contests the boundaries between the material and the spiritual, and how these writers challenge the eucharistic idea of union between Christ and the community of believers.